The In-Group Versus The Out-Group: The Impact Of Village Politics On Community Social Conditions - Muhammad Saleh; Wahyudi, Gemuh Surya Wahyudi; Rohimi (Universitas Islam Negeri (UIN) Mataram, 2023)
Diferences in a political are indeed commonly interpretated. In this research examine the impact of village politics againt the loss of social solidarity which also caused the proccess of the formation of social groups with each other.In this study researchers used field research with an ampirical approach with data collection methode namely is interview, observation and docuementation with the objectives of research to determine the social facts of the loss of social solidarity society the impact of the villages Politicsshoutwest Praya District Cebtral of Lombok. Result and discussion. First, the impact of village politics raises the proccess of forming social groups in society. Second, the loss of social solidarity and community identity. Third, the impact of village politics resluted in a breaktrough or penetration that triggers community religius patterns that are starting to be deferent and makes limination in in carrying out their religious acivities with different groups in village politics.Fourth, changes in the pattern of community behavior in caryying out culture activities that are constanly run collectively and harmoniously from a long time and now each of their groups